Palestine-Israel Conflict Resolution Analysis Study in the Perspective of Islamic History - Ihwanarotama Bella Indriasandi; Wildana Wargadinata (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The Palestinian-Israeli conflict lasted over half a century and has widely influenced international political currents. This article aims to unravel the roots of the Palestinian-Israeli conflict, explain alleged Israeli-American and American-Arab conspiracies, and solve the peace process in the match, which all failed. This research uses qualitative research methods by utilizing a narrative approach. The data collection technique used is library research with much secondary data, including scientific articles and textbooks related to the Palestinian-Israeli conflict. These data are collected, validated, arranged in similar groups, and processed data analysis using content analysis methods. The results show that Palestine is getting worse in the face of Israel, while Israel is getting stronger in armaments, economy and gaining support from major powers such as the United States, Britain, and France. The research also found that the Jewish bill submitted by Benjamin Netanyahu to the Israeli Parliament can potentially increase the number of Jews and reduce the rights of Arab Muslims as a minority community. In addition, the number of groups in Palestine hindered the country’s unity and resulted in the exodus and deportation of Muslims with former Israeli citizenship.Keywords – Analysis Study, Conflict, Islamic History, Palestine-Israel.